EFEKTIVITAS BAHAN AJAR â€œMARI MEMBACA CEPATâ€ PADA PEMBELAJARAN MEMBACA CEPAT DAN PEMAHAMAN SISWA KELAS V SD NEGERI - Inawati, Inawati; Sanjaya, Muhamad Doni (Lentera: Jurnal Ilmiah Kependidikan, 2017)
This experience is aims to describe the effect of potential in teaching materials Lets Reading more the fast to results of research development. The method used experiment. The sample of the study amounted to 251 students. Technique of collecting the data is using test. The result of the research shows that teaching materials of development result have positive effect to the improvement of fast reading ability and students understanding. This is evident from the results of statistical tests using SPSS 16 that SDN 1 OKU shows the mean value on pretest and postes is 24.318 with standard deviation of 14.043 and sig (2-tailed) 0.00. In SDN 3 OKU the mean value on pretest and postes is 20,000 with standard deviation of 12.302 and sig (2-tailed) 0.00. SDN 4 OKU shows the mean value on pretest and postes is 19.167 with standard deviation of 14.417 and sig (2-tailed) 0.00. SDN 5 OKU shows the mean value on pretest and postes is 27.727 with standard deviation of 15.409 and sig (2-tailed) 0.00. SDN 11 OKU shows the mean value on pretest and postes is 22 with standard deviation of 15.625 and sig (2-tailed) 0.00. SDN 12 OKU shows the mean value on prets and postes is 17,931 with standard deviation of 12,643 and sig (2-tailed) 0,00. SDN 18 OKU shows the mean value on pretest and postes is 18.84 with standard deviation of 13.95 and sig (2-tailed) 0.00. SDN 24 OKU shows the mean value on pretest and postes is 25.45 with standard deviation of 11.75 and sig (2-tailed) 0.00. From the results of the analysis the number 0.00 is smaller than the alpha value of 0.05. Thus, a significant difference between the value before and after the student uses the Let Reading Material. This means learning materials Lets Reading more the fast be appropriate for elementary school students of OKU Regency.